Considering the relationship between research and practice in technology education: A perspective on future research endeavours - Seery, Niall; Kimbell, Richard; Buckley, Jeffrey; Phelan, Joseph (Design and Technology Education: An International Journal, 2019)
Technology subjects are a relatively recent addition to the discipline offerings at postprimary level, and have a short but interesting history in terms of associated educational research. In this paper, an overview of the evolving research agendas that emerged in response to the nature of practice, from the perspectives of the Technology Education Research Unit (TERU) and the Technology Education Research Group (TERG) is presented. A chronological account of their research activities is provided, demonstrating the perspectives, paradigms and foundations of their research endeavours. The purpose of this paper is to provoke reflection on the past, present and future of technology education research and practice, using both TERG and TERU for narrative purposes. Therefore, this paper concludes by sharing the evolution of research in TERU and TERG, so as to help consider and shape the future of relevant, contemporary, and progressive research activity.